Diversidade e composição da vegetação ao longo de um gradiente sucessional na caatinga - Conceição, Giselle Gomes (2014)
The species composition of the vegetation of Caatinga in three successional stages was characterized by sampling 20 installments, with 20x20m (400m2), in each stage.The initial stage corresponds to areas abandoned for nearly three years, the city of Poco Redondo; intermediate stage is located in the Monumento Natural Grota do Angico situated between the cities of Caninde do Sao Francisco and Poco Redondo, this site is in forest regeneration just over 20 years; and the late stage belongs to the Caatinga fragment found in the Fazenda Sao Pedro, Porto da Folha, which does not suffer human action for over 60 years.All subjects were considered from shrub - woody stratum with CAP (circumference at breast height 1.30 m)> 6 cm, had measured its circumference and height. The additive partitioning model used corresponds to the following formula: × = £ + Ò1 + Ò2, where × is the total diversity, £ is the mean diversity within plots, Ò1 is the diversity between plots of the same area, Ò2 is the diversity between the three areas.In the inicial area 15 species belonging to 8 families and 15 genera were identified. The density and total dominance found in this area were equivalents 818,75ind./ha and 0.89 m2/ha, respectively. The species with the highest importance value was Poincianella pyramidalis. The diversity index of Shannon-Wiener (H ´) and equability index of Pielou (J´) for this area were, respectively, 0.72 and 0.61. The intermediate area showed 15 families, 25 genera and 25 species. The total density was 1611.3 ind/ha, and total dominance was 3.31 m2/ha. P. pyramidalis was the species that showed the highest values of relative density, frequency, dominance and VI. The diversity index was 0.74 and the equability was 0.53. In the area in late stage 22 families, 40 genera and 46 species were identified. The total density was 2741.3 ind/ha and total dominance equal to 13.02 m2/ha. Bauhinia cheilantha had the highest VI. The H ´and J´ indices were 1.07 and 0.64, respectively. The results of the GLM from model ANOVA confirmed that the three areas differ from each other.The graphs obtained from NMDS showed from the ordering of the points that the areasare different in species richness. The analysis of additive partitioning of diversity showed that the £ component was the least contributed to the diversity ×, but the observed value for this component was higher than expected by the null model. The component Ò1 observed was lower than expected by the model, which illustrates the grouping of species generated by the limit of dispersion the same, which hampers migration among the remaining Caatinga.The component that best contributed to the diversity × was Ò2, highlighting the importance of replacement of species along the successional process.